Comparison of Self-Expanding Stents With Distal Embolic Protection to Balloon-Expandable Stents Without a Protection Device in the Treatment of Symptomatic Vertebral Artery Origin Stenosis: A Prospective Randomized Trial. (June 2015) - Geng, Xiaokun; Hussain, Mohammed; Du, Huishan; Zhao, Liang; Chen, Jian; Su, Wei; Ma, Linlin; Gao, Zongen; Ding, Yuchuan; Ji, Xunming
Purpose: To compare the angiographic and clinical outcomes of self-expanding stents (SES) with distal embolic protection devices (EPD) vs balloon-expandable stents (BES) without EPD in the treatment of symptomatic atherosclerotic vertebral artery ostial stenosis (VAOS).Methods: Between July 2011 and March 2013, a prospective randomized trial was conducted involving 127 patients (mean age 67.3±10.2 years; 94 men) with symptomatic VAOS randomly assigned to treatment with SES + EPD (Precise RX or RX Acculink stent + Spider FX EPD; n=61) or BES (Palmaz Blue or Resolute RX; n=66) without EPD. In-stent restenosis (ISR) >50% detected by duplex ultrasound was the primary endpoint. Technical success, clinical success, complications within 30 days, and signal intensity abnormalities on diffusion weighted imaging (DWI) after stenting were compared.Results: The 30-day technical success rate was 95.5% (63/66) for SES+EPD vs 100% (70/70) for BES without EPD (p=0.072). DWI at 24 hours poststenting showed 2 hyperintense lesions in 2 (3.3%) SES + EPD cases and 15 hyperintense lesions in 13 (18.6%) BES patients (p<0.01). At a mean 18-month follow-up, the clinical success rate was 93.9% (62/66) for the SES + EPD group vs 85.7% (60/70) for the BES group (p=0.115). The ISR was seen in 16/70 (22.9%) arteries in the BES group and 2/66 (3.1%) arteries in SES + EPD group (p<0.01). Target vessel revascularization was performed in 7 (10.0%) BES arteries vs none in the SES + EPD group (p<0.01).Conclusion: SES with EPD in the treatment of symptomatic VAOS is technically feasible and safe, with low rates of ISR and significantly reduced thromboembolic events on imaging when compared to BES without EPD.